The costs of macroprudential deleveraging in a liquidity trap - Jiaqian Chen; Daria Finocchiaro; Jesper Lindé; Karl Walentin (Sveriges Riksbank, 2021)
What are the effects of different borrower-based macroprudential tools when both real and nominal interest rates are low? We study this question in a New Keynesian model featuring long-term debt, housing transaction costs and a zero lower bound constraint on policy rates. We find that the long-term costs, in terms of output losses, of all the macroprudential tools we consider are moderate. However, the short-term costs differ substantially between tools. Moreover, the costs vary depending on the current state of economy and monetary policy. Specifically, a loan-to-value tightening is more than three times as contractionary compared to a loan-to-income tightening when debt is high and monetary policy cannot accommodate.
Keywords: E52; E58; 330; Household debt; Zero lower bound; New Keynesian model; Collateral andborrowing constraints; Mortgage interest deductibility; Housing prices